Enhancing Entrepreneurial Expectations Through Financial Literacy - Nike Silvia Dewi (Arthatama: Journal of Business Management and Accounting, 2024)
Entrepreneurial success is closely linked to financial literacy, as effective financial administration enables entrepreneurs to manage resources, mitigate risks, and optimize business growth. This study explores the impact of financial literacy on the entrepreneurial expectations of Digital Business students, emphasizing the role of financial knowledge in shaping confidence and decision-making capabilities. Using a conceptual analysis approach, this research reviews existing literature to establish a theoretical framework linking financial administration with entrepreneurial ambition. Findings indicate that financial literacy enhances students’ ability to develop sound business strategies, adapt to financial challenges, and sustain long-term business operations. Furthermore, integrating financial education into entrepreneurship curricula is essential to prepare students for the dynamic business environment. The study underscores the necessity of equipping future entrepreneurs with financial management skills, ensuring they can navigate financial complexities effectively. By fostering financial literacy, educational institutions can contribute to a more resilient and innovative entrepreneurial ecosystem.